Deltaarenes; novel macrocyclic molecules that are readily available from 1, 4-benzoquinone and benzene dithiols. Issue 38 (20th September 2018) - Kamimura, Akio; Watanabe, Ryusuke; Fukumitsu, Tomoki; Ikeda, Kazuki; Kawamoto, Takuji; Sumimoto, Michinori; Mori, Shigeki; Uno, Hidemitsu
Abstract: New types of macrocyclic compounds, deltaarenes, are prepared. The compounds were readily synthesized in three steps from an arenedithiol and benzoquinone, and the yields of the macrocyclization reaction reached up to 40% under high dilution conditions. X-ray crystallographic analysis revealed that the macrocycle has a relatively rigid trimeric structure with a unique triangular hole, the size of which was approximately 11 Å along each side. NMR data suggests that the ring has a C3-symmetric structure. The X-ray analysis showed that the hole is large enough to capture one molecule of chlorobenzene. Use of a variety of dithiols allowed the synthesis of different types of deltaarene derivatives. MO calculations showed that the hole size depends on the dithiol unit. Deprotection of the twelve methoxyl groups was easily achieved by treatment with BBr3 and yielded the free-OH deltaarene derivative. Graphical abstract: Image 1